1983
DOI: 10.1161/01.hyp.5.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic alpha- and beta-adrenoceptor stimulation and norepinephrine release in the spontaneously hypertensive rat.

Abstract: SUMMARY The present study was designed to measure norepinephrine release during sympathetic nerve stimulation and evaluate the presynaptic inhibitory and facilitatory actions of a-adrenoceptor and /3-adrenoceptor agonists respectively, in the isolated perfused kidney of normotensive WistarKyoto (WKY) and spontaneously hypertensive rats (SHR). Periarterial nerve stimulation (0.25 to 32 Hz) caused a significantly greater release of norepinephrine, which was measured as total tritium overflow, in the SHR. The vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Our present results are in agreement with those re ported by Ekas et al [5] who also found a similar presynaptic (3-receptor function in NR and SHR. For the mes enteric vascular bed of the SHR, however, it was shown that the (32-adrenoceptor-mediated facilitatory modula tion of vascular neurotransmission was enhanced com pared with that of NR [4].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our present results are in agreement with those re ported by Ekas et al [5] who also found a similar presynaptic (3-receptor function in NR and SHR. For the mes enteric vascular bed of the SHR, however, it was shown that the (32-adrenoceptor-mediated facilitatory modula tion of vascular neurotransmission was enhanced com pared with that of NR [4].…”
Section: Discussionsupporting
confidence: 94%
“…Whether these prejunctional p-receptors are modified in SHR is debatable; an enhanced presynaptic P-adrenoceptor-mediated modulation of adrenergic neurotrans mission has been reported for the perfused mesenteric bed of SHR [4], whereas an unchanged presynaptic Padrenoceptor function was reported for the perfused kid ney of SHR [5].…”
Section: Introductionmentioning
confidence: 99%
“…Yohimbine adminis tration to SHR produces a significant reduc tion in renal NE content down to WKY lev els [38]. Other studies also confirm an al tered renal responsiveness to a 2-adrcncrgic drugs in the SHR when compared to the WKY [39], Thus, the changes in Ra2AR number in the SHR correlates with func tional abnormalities.…”
Section: Discussionmentioning
confidence: 85%
“…5 -8 In light of the influence of the sympathetic nervous system on sodium and water reabsorption and renovascular tone, the potential importance of the renal nerve in the pathogenesis of experimental hypertension is well recognized. 9 - 10 Particularly compelling is evidence that efferent renal nerve activity is elevated andjunctional norepinephrine release is enhanced 11 …”
mentioning
confidence: 99%